IUGR Management: New Perspectives - N. Giuliano; M. L. Annunziata; S. Tagliaferri; F. G. Esposito; O. C. M. Imperato; M. Campanile; M. G. Signorini; A. Di Lieto (Journal of Pregnancy)
Aim of the Study. Analyzing velocimetric (umbilical artery, UA; ductus venosus, DV; middle cerebral artery, MCA) and computerized cardiotocographic (cCTG) (fetal heart rate, FHR; short term variability, STV; approximate entropy, ApEn) parameters in intrauterine growth restriction, IUGR, in order to detect early signs of fetal compromise. Population Study. 375 pregnant women assisted from the 28th week of amenorrhea to delivery and monitored through cCTG and Doppler ultrasound investigation. The patients were divided into three groups according to the age of gestation at the time of delivery, before the 34th week, from 34th to 37th week, and after the 37th week. Data were analyzed in relation to the days before delivery and according to the physiology or pathology of velocimetry. Statistical analysis was performed through the t-test, chi-square test, and Pearson correlation test (P<0.05). Our results evidenced an earlier alteration of UA, DV, and MCA. The analysis between cCTG and velocimetric parameters (the last distinguished into physiological and pathological values) suggests a possible relation between cCTG alterations and Doppler ones. The present study emphasizes the need for an antenatal testing in IUGR fetuses using multiple surveillance modalities to enhance prediction of neonatal outcome.